R-operation of Bogolyubov—Parasyuk and operator expansions in mass-free theories - Zaviyalov, О. I.; Polivanov, М. K. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The methods of the Bogolyubov-Parasyuk $R$-operation are applied to construct operator expansions in massless quantum field theories.